Cu(I)-catalyzed coupling of diaryldiazomethanes with terminal alkynes: an efficient synthesis of tri-aryl-substituted allenes. Issue 49 (9th December 2015) - Wu, Chenggui; Hu, Fangdong; Liu, Zhenxing; Deng, Guisheng; Ye, Fei; Zhang, Yan; Wang, Jianbo
Abstract: A highly efficient method for the synthesis of tri-aryl-substituted allenes has been developed through Cu(I)-catalyzed coupling of diaryldiazomethanes with terminal alkynes. The reaction is under mild conditions and uses simple and inexpensive CuI as the catalyst. Mechanistically, the reaction follows a pathway involving Cu(I) carbene migratory insertion. Graphical abstract: